A Study of Prevalence of Hypoythyroidism during the First Trimester in Pregnancy - دعبول, ديانا; أريج بوبو; أحمد عبد الرحمن (Latakia University Journal -Medical Sciences Series, 2024)
Background: Maternal hypothyroidism is the most common thyroid disorder during pregnancy.maternal hypothyroidism especially in the first trimester leads to a lack of availability of thyroid hormone during the basic stage of brain development in the fetus. It is also associated later with increased rates of miscarriage, stillbirth, congenital malformations, and increased perinatal mortality. This research mainly aims to study the prevalence of hypothyroidism during the first trimester of pregnancy. Methods: The study included 120 pregnant women in the first trimester of pregnancy who visited the Department of Obstetrics and Gynecology at Tishreen University Hospital during the period from March 2023 to March 2024. Results: The mean age of the pregnant woman was: 25.32 years, mean gestational age: 6 weeks, mean BMI: 24.9, mean TSH: 2.44 miu/l, mean FT4: 15.42 pmol/l, the normal reference range of TSH during the first trimester of pregnancy: 0.1 – 2.5 miu/l The prevalence of hypothyroidism was 25.8%, of which 23.3% were subclinical hypothyroidism and 2.5% were clinical hypothyroidism. It was also noted that the prevalence of hypothyroidism increased with increasing age of the pregnant woman and increasing body mass index. Conclusion: this study concludes that there is a high prevalence of hypothyroidism majority being subclinical in pregnant women during the first trimester of pregnancy and universal screening of hypothyroidism may be desirable during pregnancy.